Tinjauan Literatur Sistematis tentang Dinamika Politik Organisasi dan Penggunaan Kekuasaan Pemimpin dalam Memicu Sikap Diam Karyawan - Zaid Abdul Hamid; Berdhy Ursila Djamil; Muhammad Irfan Fauzan; Sofa Parihah Nurasiah (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to comprehensively examine the simultaneous interaction effect of organizational political dynamics and the use of leader power on the emergence of employee silence. Workplace silence is not merely a form of passivity, but a strategic and rational decision by employees to withhold vital information due to significant sociopolitical risks. This research employs the Systematic Literature Review (SLR) method, adopting the eight structured stages of the Okoli (2015) protocol. Through this method, the study filtered and analyzed 24 relevant empirical and theoretical literatures. The review concludes that a work environment dominated by negative political maneuvers acts as a situational vulnerability vessel. This vulnerability turns into a crisis when leaders respond to these dynamics using a repressive, coercion-based leadership style (hard power). The convergence of this toxic culture and destructive leadership directly destroys psychological safety and triggers severe emotional exhaustion, forcing employees to remain silent as a self-defense mechanism. This study provides managerial implications regarding the importance of mitigating the political climate, transforming towards adaptive leadership, and providing reporting channels that guarantee employees' psychological safety.